2015
DOI: 10.3402/ijch.v74.25697
|View full text |Cite
|
Sign up to set email alerts
|

Air ambulance and hospital services for critically ill and injured in Greenland, Iceland and the Faroe Islands: how can we improve?

Abstract: The Nordic Atlantic Cooperation (NORA) is an intergovernmental organization under the auspices of the Nordic Council of Ministers. The NORA region comprises Greenland, Iceland, Faroe Islands and western coastal areas of Norway. Historical, cultural and institutional links bind these nations together in multiple ways, and regional co-operation has in recent years become a focus of interest. This commentary addresses air medical services (AMSs) and available advanced hospital services in the 3 smallest NORA coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The barriers to medical travel can be overwhelming, leading to delays in receiving care, or an avoidance of care-seeking altogether,37 resulting in poorer outcomes and higher costs for aggravated health conditions 38. One study of medical travel in Arctic regions of Nordic countries estimated that the number of service hours per Northern patient is 2–3 times higher than urban populations 39. Continuity of care remains a challenge in the North; with only 31.1% of Indigenous territorial residents seeing a regular doctor, compared with 76.4% of Indigenous people outside the territories 40.…”
Section: Discussionmentioning
confidence: 99%
“…The barriers to medical travel can be overwhelming, leading to delays in receiving care, or an avoidance of care-seeking altogether,37 resulting in poorer outcomes and higher costs for aggravated health conditions 38. One study of medical travel in Arctic regions of Nordic countries estimated that the number of service hours per Northern patient is 2–3 times higher than urban populations 39. Continuity of care remains a challenge in the North; with only 31.1% of Indigenous territorial residents seeing a regular doctor, compared with 76.4% of Indigenous people outside the territories 40.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals living in the Circumpolar North may have to travel extensive distances to reach other cities or even other countries for the health services they need, especially if these are specialised services [11,[14][15][16]20,22,28,31,32]. For example, researchers found that some patients living in Greenland must endure 6 to 7 h of travel time to gain access to advanced care in Denmark [15]. The distance of the communities from specialised healthcare services can place stresses on patients as well as healthcare providers.…”
Section: Distance To Urban Centresmentioning
confidence: 99%
“…Weather and seasonal conditions Ten articles directly addressed weather conditions that can affect individuals' ability to gain access to healthcare services by limiting safe travel for both patients and healthcare providers [15,18,19,27,[33][34][35][36][37][38]. For example, in rural Alaskan communities, "it is not uncommon for airplanes to be grounded for low visibility due to fog, high winds, horizontal rains, or low clouds" [37, p. 11].…”
Section: Distance To Urban Centresmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the new system was in an early stage of implementation at the time of the survey, it is possible that some areas of concern would have been addressed as providers become more acquainted with the new system. The NWT shares the challenges in other remote air ambulance systems such as limited resources, unpredictable weather conditions and long distances separating suitable landing sites ( 26 ). Our findings reveal that accurate information exchange between providers along the trajectory of the evacuation is critical, from the initial phone contact describing the clinical condition of the patient to documenting in-transit care and conveying aeronautical information such as being notified of the estimated time of arrival of the plane.…”
Section: Discussionmentioning
confidence: 99%